Specific pattern of bone scan as a Result of Unintentional-Intraarterial Injection Into the Ulnar Artery - Amir Gholami; Iraj Jafaripour (Babol University of Medical Sciences, 2022)
Background: Bone scintigraphy with 99mTc labeled radiopharmaceuticals is a valuable method in nuclear medicine for assessing the bony structure. In clinical setting, bone scintigraphy is accomplished after the injection of 99mTc labeled diphosphonate complexes into a peripheral vein. Inadvertent intra-arterial injection on the antecubital region may cause a special form of artifacts leading to problems inaccurately interpreting these studies as functional images. Case Presentation: We present a 44-year-old man with history of chest wall pain for bone scintigraphy as part of a work-up for determining the pain source. The patient received an injection of 740MBq 99mTc-methylene diphosphonate (MDP) into a blood vessel at the right forearm. Two hours later, an increased uptake of activity was observed on the right forearm and ulnar half of the wrist-hand in the whole body and spot images. The scan findings were consistent with the anatomical and physiological expectations of the ulnar arterial perfusion range. This case displays that an incidental injection with a 99mTc labeled diphosphonate into the ulnar artery results in a hot ulnar half of the palm and ulnar-sided three digits, because these areas are directly exposed to radiopharmaceutical, therefore more radiopharmaceutical is deposited. Conclusion: It is important for the physician, and especially for the nuclear medicine technician, to know the specific appearance created in the bone scan due to such an event so that they do not make a diagnostic mistake.